Venovenous extracorporeal membrane oxygenation: early CT alterations following use in management of severe respiratory failure in neonates. - Brunberg, J A; Kewitz, G; Schumacher, R E (American Journal of Neuroradiology, 1993)
PURPOSE To describe brain CT alterations occurring after neonatal venovenous extracorporeal membrane oxygenation (V-V ECMO).METHODS CT studies were prospectively obtained after V-V ECMO in 31 neonates with severe respiratory failure. Images were scored for cerebrospinal fluid space size, hemorrhage, and regions of decreased attenuation.RESULTS Subarachnoid space enlargement at the interhemispheric fissure, frontal, temporal, or parietal convexity occurred in 21 of the 31 patients. When subarachnoid space enlargement was asymmetric (six of the 21), it was always isolated to or greater on the right. Ventricular enlargement was demonstrated in seven of the 31. Hemorrhage occurred in seven and regions of low brain attenuation in 11 of the 31 neonates.CONCLUSIONS Increased sagittal sinus pressure caused by internal jugular vein ligation and cannulation of the superior vena cava may contribute to subarachnoid space enlargement by decreasing cerebrospinal fluid resorption at the arachnoid villi. Reduced incidence of cerebral hemorrhage with V-V ECMO, as compared with venoarterial (V-A) ECMO, may relate to sparing of the right common carotid artery (it is ligated with V-A ECMO), and to routing of oxygenated blood to the right atrium with V-V ECMO rather than to the arterial circuit as with V-A ECMO.